'European Exceptionalism' and nuclear third party liability. (1st January 2011) - Handrlica, Jakub
In Europe, we are currently facing a labyrinth of international treaties that create a number of different regimes in nuclear liability. The problem can also be seen as part of a more complex process, which has been described as ' European Exceptionalism ' in the literature. This paper deals with the problem from two points of view. First, it will deal with the question of whether the accession of Euratom to a liability convention will be a viable option and what kind of implications such a step will have. Second the issue will be dealt concerning a potential nuclear liability directive, as well as its implications upon commitments to these nuclear liability treaties. At the end, the most sensitive part of questions will be addressed: implications of potential conflict between commitments arising from such a directive and from the existing international agreements.